"I'm Grateful, but Am I?": The Exploration of Gratitude as a Complex Experience Among Malaysian Cancer Patients. (April 2023) - Hussin, Nur Atikah Mohamed; Mohammad, Taufik; Jamaludin, Shariffah Suraya Syed
Gratitude has gained attention among health researchers for its benefits among chronic illness. However, most of the studies were focusing on the positive effects, neglecting the complex dimensions of gratitude that can contribute to both opportunities and challenges for chronic illness patients. This study aims to understand gratitude among cancer patients in Malaysia from a sociocultural perspective. This includes understanding how cancer patients view gratitude and the impacts of gratitude throughout their cancer-battling journey. This qualitative study involved 35 cancer patients. A thematic analysis was done to analyze the collected data. Among the themes discovered were searching for meaning, meaningful experience, gratitude through the enrichment activities, and gratitude as religious cultural expectations. This study suggests that gratitude is an important experience for chronic illness patients. The ability to understand this experience is vital to support and empower the patients throughout their daily lives.